Hair styling procedures and hair morphology: A clinico-microscopic comparison study - Ram H Malkani; Seema M Shirolikar; Suman Karmakar; Maninder Singh Setia (Wolters Kluwer Medknow Publications, 2020)
Background: The present study is a cross-sectional comparison to evaluate the association between hair loss and hair structural changes (gross and microscopic), and hairstyling procedures in women. Methods: We included 94 women; and collected data on sociodemographics, clinical history, sun-exposure, and hair-product use history. Women who reported blow drying of hair, hair straightening, use of hair iron or perming in the past 6 months were classified as cases. Age matched (±2 years) women who did not report any of the above procedures in the past 6 months were controls. The following tests were done: hair pull test; hair density assessment; hair breakage index (HBI); and microscopic examination. A logistic regression model was used for estimation of the odds ratio (OR) and 95% confidence intervals (CI). Results: The mean (standard deviation [SD]) age in the case and control group was 26.4 (6.3) and 27.4 (6.3) years, respectively (P = 0.43). There was no significant difference in the mean (SD) HBI (1.05 [0.08] vs 1.07 [0.05], P = 0.22) or hair density (3.28 [0.41] vs 3.16 [0.39], P = 0.19). Cases were significantly more likely to have microscopic changes compared with controls (OR: 22.0, 95% CI: 4.3, 112.6; P < 0.001). Sun exposure for more than 3 h was significantly associated with microscopic changes (OR: 6.7, 95% CI: 1.2, 39.1; P = 0.03). Conclusion: Women with hairstyling procedures in the past 6 months were more likely to have microscopic changes, even though there was no difference in the hair assessment parameters. Specific guidelines on use of hairstyling procedures for Indian hair should be developed.